Tobacco Industry Employment: A Review Of The Price Waterhouse Economic Impact Report And Tobacco Institute Estimates Of "Economic Losses From Increasing The Federal Excise Tax" (Tufts Archival Research Center, 2007)
Review of a 1992 Price Waterhouse report and subsequent Tobacco Institute-produced documents on estimated economic losses resulting from federal excise tax. Finds employment and job loss figures in Price Waterhouse and Tobacco Institute documents to be grossly inflated. Cites methodological errors and biased analyses. Explains problems within the reports at length.